Exploring the Gut Microbiota–Retina Axis: Implications for Health and Disease - Nicola Schiavone; Giulia Isoldi; Sara Calcagno; Elisabetta Rovida; Emiliano Antiga; Carolina Vieira De Almeida; Matteo Lulli (Microorganisms)
The gut microbiota represents a rich and adaptive microbial network inhabiting the gastrointestinal tract, performing key functions in nutrient processing, immune response modulation, intestinal wall protection, and microbial defense. Its composition remains highly personalized and responsive to external influences, including lifestyle patterns, physical activity, body composition, and nutritional intake. The interactions of the gut microbiota with bodily systems are conventionally interpreted as broad systemic impacts on organ balance. Yet, emerging research—exemplified by the gut microbiota–brain axis—suggests the potential existence of more targeted and direct communication mechanisms. Dysbiosis, characterized by microbial ecosystem disturbance, generates multiple metabolic compounds capable of entering systemic circulation and reaching distant tissues, notably including ocular structures. This microbial imbalance has been associated with both systemic and localized conditions linked to eye disorders. Accumulating scientific evidence now supports the concept of a gut–retina axis, underscoring the significant role of microbiota disruption in generating various retinal pathologies. This review comprehensively investigates gut microbiota composition, functional dynamics, and dysbiosis-induced alterations, with specific focus on retinal interactions in age-related macular degeneration, diabetic retinopathy, glaucoma, and retinal artery occlusion. Moreover, the review explores microbiota-targeted therapeutic strategies, including precision nutritional interventions and microbial transplantation, as potential modulators of retinal disease progression.